Clinical, Pathological, Laboratory Characteristics, and Treatment Regimens of Kimura Disease and Their Relationships With Tumor Size and Recurrence - Fan, Lina; Mo, Shiyan; Wang, Yanyan; Zhu, Jian (Frontiers in Medicine, 2021)
Objective: As of date, Kimura disease (KD) has an unclear etiology, no accepted diagnostic standard, and no definite treatment regimen. In this study, clinical and pathological laboratory characteristics as well as treatment regimens of patients with KD with different tumor sizes and status of tumor recurrence were analyzed. This was performed to identify the factors determining tumor size and recurrence as well as to identify effective treatment methods for patients with KD. Methods: A total of 33 hospitalized patients with a definite diagnosis of KD were enrolled in this study. Results: There were 15 patients (45.5%) with a maximum tumor diameter of <3cm. There were no statistically significant differences in age, gender, clinical symptoms, lesion sites, laboratory indicators and treatment regimens between patients with a maximum tumor diameter <3cm or ≥3cm (P>0.05). Among the 25 patients who completed the follow-up, there were 18 patients (72%) who had a recurrence of KD. There were no statistically significant differences in age, gender, clinical symptoms, the maximum tumor diameter, lesion sites, laboratory indicators and initial treatment regimens between patients with or without the recurrence of KD (P>0.05). There was a statistically significant difference in systolic blood pressure (SBP) between patients with or without the recurrence of KD (P<0.05). All patients who received only surgical treatment had disease recurrence, 33.3% of patients who received prednisone therapy had no disease recurrence, and 37.5% of patients who received combination therapy showed recurrence. Conclusion: The current study summarized clinical manifestations, pathological features, laboratory indicators, and treatment regimens of patients with KD. There were no significant differences in these aspects among patients with different tumor sizes, and no significant difference in these aspects except in the SBP between patients with or without the recurrence of KD, indicating that SBP is a significant clinical factor affecting disease recurrence in patients. Combination therapy with prednisone was found to be superior to surgical treatment.